Trao đổi xã hội và nhận thức xã hội trong đồng tạo sinh dịch vụ: Một nghiên cứu về dịch vụ du lịch tại TP. Hồ Chí Minh - Pham Thanh , Tien; Nguyen Manh , Tuan (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2020)
Customer co-creation is a key topic of service research with the two highlights are service value always resides in social systems and customers, along with firms, play the role of social actors who are capable to apply their competencies for the benefit of others. In the travel service, the paper proposes a structural model of customer co-creation behavior in which both social exchange (interactional justice, customer-to-customer interaction, affective commitment) and social cognitive (self-efficacy) act as its antecedents and both perceived value and quality of life represent its outcomes in terms of individual customer benefits and repurchase intention indicates its effect in terms of firm benefit. A survey study with PLS of 298 customers from 7 tourism companies based in Ho Chi Minh City showed that all of 13 proposed hypotheses are supported. The proposed model explained 59.8% of variance of co-creation behavior, and 40.6% of variance of repurchase intention.
Keywords: Co-creation; Social exchange; Social cognitive; Quality of life; Repurchase intention; Travel service